Mengukur Tingkat Kepuasan Nasabah Dampak Dari Kualitas Pelayanan dan Citra Perusahaan - Meryawan, I Wayan; Fitriandari, Mahayanti; Kesuma Suryawan, Tjokorda Gde Agung Wijaya; Indah Widiantari, I Dewa Ayu (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
Placing customer satisfaction as the primary objective or central aim of the company both in the present and for the future holds immense importance due to its pivotal role in upholding the longevity of the offered products or services. Employing strategies that focus on the quality of service and bolstering the company's reputation are recognized as effective means to amplify customer contentment with the products or services they avail. The present study endeavors to assess the interplay and individual impacts of service quality and company image on customer satisfaction within KSP Sri Baruna Lestari located in Bangli Regency. The study population encompasses all active customers who utilized savings, deposits, and credit services at KSP Sri Baruna Lestari during the year 2021, amounting to a total of 2,385 individuals. The sample size was determined utilizing the Slovin Formula, resulting in a sample comprising 96 individuals selected through purposive random sampling. The analytical techniques employed in this research encompass classical assumption tests, multiple linear regression analysis, determination analysis, F-test, and t-test. The research outcomes divulge that both service quality and company image exert a concurrent and positive significant influence on customer satisfaction. Furthermore, it is found that service quality and company image exert partial yet positive and significant impacts on customer satisfaction at KSP Sri Baruna Lestari.